Overcoming spectral overlap via inductively coupled plasma-tandem mass spectrometry (ICP-MS/MS). A tutorial review. Issue 9 (24th February 2017) - Bolea-Fernandez, Eduardo; Balcaen, Lieve; Resano, Martín; Vanhaecke, Frank
Abstract : This work reviews the operating principles of ICP-tandem mass spectrometry (ICP-MS/MS) and the key applications reported on since the introduction of the technique in 2012. Abstract : This work reviews the operating principles of ICP-tandem mass spectrometry (ICP-MS/MS) and the key applications reported on since the introduction of the technique in 2012. The main differences between single quadrupole ICP-MS and ICP-MS/MS are elucidated and the tools available for method development are addressed. Examples of real-life applications are given to demonstrate the capabilities of this novel setup in the context of elemental, speciation and isotopic analysis. Attention has been paid to the different approaches (on-mass and mass-shift) allowing interference-free conditions to be obtained.